Antibacterial Effect of Curcumin against Clinically Isolated Porphyromonas gingivalis and Connective Tissue Reactions to Curcumin Gel in the Subcutaneous Tissue of Rats - Sha, Aram Mohammed (Biomed Res Int, 2019)
The aim of this study was to find the antibacterial potential of curcumin against Porphyromonas gingivalis and connective tissue responses to curcumin gel in the subcutaneous tissue of rats. The sample consisted of subgingival plaque collected from patients with chronic periodontitis. The P. gingivalis clinically isolated strain was confirmed by anaerobic culture, morphology, biochemical tests (Vitek ANC Kit), and PCR (16S rDNA). Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by incubation of twofold serial dilution of broth media containing curcumin (from 100 to 0.05 µg/ml) for 48 h at 37°C. Fifteen adult Wistar rats (3-4 months old) were used and randomly divided into three groups (negative control, positive control, and experimental groups). Tubes were implanted on the back skin (45 tubes). Rats were euthanized at 7, 30, and 60 days after surgical processes, and then the samples were taken and processed to achieve conventional hematoxylin and eosin-stained slides. The MIC and MBC of curcumin against clinically isolated P. gingivalis were 12 µg/ml. Curcumin gel caused moderate inflammatory reactions at 7 and 30 days, while at 60 days, it caused dramatic decline and resulted in a nonsignificant response. Besides, curcumin gel stimulated quick reepithelialization, fibroblast proliferation, and scarring through the formation of thick bundles of well-organized collagen fibers. Curcumin has an effective antibacterial action against clinically isolated P. gingivalis at low concentration (12 µg/ml), and it was regarded as the biocompatible material in the subcutaneous tissues.